Contributos para a compreensão da população desempregada: o papel dos padrões de crenças motivacionais - Ferreira, Joaquim Armando (2010)
This article focuses on a phenomenon that has been worrying the current society - unemployment, considering and clarifying concepts associated with this phenomenon. Thus, it will be made a brief discussion on the emergence of the problem, namely the socio-economic situation of present times, as well as analyzing the changes in the concept of career. In an attempt to understand the issues related to unemployment, one will seek to describe the impact of both unemployment and job insecurity upon individuals in order to deepen our understanding of the population unemployed. Stressing the centrality that work takes on peoples´ lives, we will also address the most important mediators of occupational reintegration, intending to make contributions toward the understanding of psychosocial factors involved in job-searching activities and consequently helping individuals in the transition from unemployment to work. KEY-WORDS: unemployment; boundaryless